Walt Disney a life from beginning to end - Hourly History (Hourly History, 2018)
The name Disney is celebrated throughout the world because of its association with blockbuster animated films and most especially iconic cartoon characters. Just about everyone on the planet, regardless of time, place, or culture, has at one time or another become acquainted with Mickey Mouse, Donald Duck, and everybody?s favorite anthropomorphic dog, Goofy. These are the characters that we know and love.
Keywords: Walt Disney